2011
DOI: 10.1016/j.jcrs.2010.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular wavefront aberrations and retinal image quality with objective accommodation

Abstract: Ocular wavefront aberrations and retinal image quality changed with accommodation in normal human eyes. Total spherical aberration changed more than other HOAs with accommodation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
2
31
2
3
Order By: Relevance
“…This aberrometer was already used in several studies. [24][25][26][27] Furthermore, some studies reported the comparability and repeatability of ray tracing aberrometers with good results. [28][29][30][31][32] However, no previous study measured the aberration of multifocal IOLs using a ray tracing-type aberrometer.…”
Section: Discussionmentioning
confidence: 99%
“…This aberrometer was already used in several studies. [24][25][26][27] Furthermore, some studies reported the comparability and repeatability of ray tracing aberrometers with good results. [28][29][30][31][32] However, no previous study measured the aberration of multifocal IOLs using a ray tracing-type aberrometer.…”
Section: Discussionmentioning
confidence: 99%
“…For a fixed pupil diameter, HOA RMS consistently increases with greater accommodation demands, although some have found this occurs only with demands above 3 D . The major consistent change in HOAs that occurs during accommodation is a decrease in primary spherical aberration (Z40), becoming less positive or more negative .…”
Section: Hoas During Near Work and Accommodationmentioning
confidence: 97%
“…During accommodation, a decrease in coma-like aberrations -Z (3) (−1), Z (3) (1) -was found; spherical aberration -Z (4) (0) -changes the sign from positive to negative [12]. The negative shift of the total spherical aberrations during accommodation is noted in other works, too [13]. On the other hand, correction of higher order aberrations alters the accommodative response [8].…”
Section: Introductionmentioning
confidence: 74%